Funding public schools in the United States, Indian Country, and US territories - Westbrook, Philip; Houck, Eric A.; Wood, R. Craig; Thompson, David C., 1951- (Conducting research in education finance., 2023)
"The National Education Finance Academy has once again convened university faculty members, state-level administrators, officials from state level chapters of the Association of School Business Officials, and others to provide a single-volume reference of school funding mechanisms for each of the states, the District of Columbia, Indian Country, and the US territories. This volume supplements the annual "state-of-the-state" profiles produced by the National Education Finance Academy so that educators, policymakers, and researchers can have access to accurate and concise information on how K12 education functions are supported across multiple jurisdictions. In addition, each profile addresses state level efforts to provide education funding to support schools during the COVID-19 pandemic. The second edition expands upon groundbreaking work in the first edition, which for the first time reported comprehensively on the multiple jurisdictions and mechanisms impacting funding for Native American students, by also reporting on policies and funding mechanisms for public schools in US Territories"--